Internal damage growth in quasi-brittle fibre-reinforced cementitious materials under cyclic compressive loading - Sagar, R. Vidya; Basu, Dibya Jyoti; Reddy, K.V. Suhas; Prathap, Y.; Bhuvaneswari, G.; Keerthi, P. Sai (Journal of Structural Engineering, 2024)
This article reports a comparison between the internal damage growth in cementitious materials without fibres andwith fibres subjected to elevated amplitude cyclic compressive loading. The damage progression was assessed usingultrasonic testing method and Acoustic Emission (AE) testing. The intricate fracture mechanism in the test specimenscauses rise to a higher harmonic generation, which was used as an indicator to the internal damage. The decrement inwave peak amplitude with higher harmonic generation may be regarded as a ‘internal damge growth’ in the deformablesolid. The complexity in the fracture mechanism in fibrous cementitious matrix influenced the heterogeneity of thespecimen, which is reflected by the steep decrement in the slope of the line plotted using normalized higher harmonicratio and load. It was observed that the ‘magnitude of the total damage’ developed in plain concrete at the last loadingphase was relatively lower than brass coated steel fibre reinforced concrete. This was supported by the damageparameter based on generated AE, where final failure of the specimens preceded an AE avalanche. Therefore, theutilization of a combination of nondestructive testing techniques such as AE and nonlinear ultrasonic testing can offera more comprehensive understanding of the progression of damage in quasi-brittle cementitious materials.